Der Ort der Karibik und Zentralamerikas in der Welt – schwache Staaten auf der Pariser Friedenskonferenz - Fischer, Thomas (Anuario de Historia de América Latina, 2018)
During World War I, the geo-political position of the nations which make up the Caribbean-Central-American region was renegotiated. From the point of view of this region, the most important change was the increase in US-interventionism, legitimized by the premises contained in the Monroe Doctrine. Concomitantly to the growth of US influence, the German, but also the British and French economic and cultural presence suffered a period of decline. Following the end of the war, the allied powers wished to implement a new organizational principle i.e. world order. The fundament of said order was the League of Nations whose Covenant was negotiated at the Paris Peace Conference between January and April of 1919. The weak Caribbean and Central American states sought to take advantage of the “Wilsonian Moment” in order to enforce their own visions and ideas. In particular, they addressed the Wilsonian principles of the right to sovereignty and self-determination valid for all states, independently of whether they were great or small, strong or weak. This paper focuses on the Caribbean and Central American delegates’ ideas, the potential and the limits to implement them in diplomatic practice and the differences between the states of the region.